Increased risk of breast cancer associated with CC genotype of Has-miR-146a Rs2910164 polymorphism in Europeans. - Hai Lian; Lei Wang; Jingmin Zhang (PLoS ONE, 2012)
BACKGROUND: Emerging evidence suggests that microRNAs play a critical role in the pathogenesis of breast cancer. Several molecular epidemiological studies were conducted in recent years to evaluate the association between has-miR-146a rs2910164 polymorphism and breast cancer risk in diverse populations. However, the results remain conflicting rather than conclusive. METHODOLOGY/PRINCIPAL FINDINGS: We performed a meta-analysis of 6 case-control studies that included 4238 breast-cancer cases and 4469 case-free controls. We assessed the strength of the association, using odds ratios (ORs) with 95% confidence intervals (CIs). Overall, this meta-analysis showed that the rs2910164 polymorphism was not associated with a significantly increased risk of breast cancer in all genetic models (for GC vs GG: OR = 1.00, 95% CI = 0.90-1.09, P(heterpgeneity) = 0.364; for CC vs GG: OR = 1.16, 95% CI = 0.98-1.36, P(heterpgeneity) = 0.757; for GC+CC vs GG: OR = 1.02, 95% CI = 0.93-1.12, P(heterpgeneity) = 0.562; for CC vs GC+GG: OR = 1.10, 95% CI = 0.96-1.26, P(heterpgeneity) = 0.441). However, in the stratified analysis by ethnicity, we found the rs2910164 polymorphism was associated with increased breast cancer risk among Europeans in homozygote comparison (CC vs. GG: OR = 1.29, 95%CI = 1.02-1.63, P(heterpgeneity) = 0.950, P = 0.032) and recessive model (CC vs. GC+GG: OR = 1.31, 95%CI = 1.05-1.65, P(heterpgeneity) = 0.839, P = 0.019). No publication bias was found in the present study. CONCLUSIONS/SIGNIFICANCE: This meta-analysis suggests, for the first time, that the CC homozygote of rs2910164 may contribute to breast cancer susceptibility in Europeans.